Membrane orientation and binding determinants of G protein-coupled receptor kinase 5 as assessed by combined vibrational spectroscopic studies. - Pei Yang; Alisa Glukhova; John J G Tesmer; Zhan Chen (PLoS ONE, 2013)
G-protein coupled receptors (GPCRs) are integral membrane proteins involved in a wide variety of biological processes in eukaryotic cells, and are targeted by a large fraction of marketed drugs. GPCR kinases (GRKs) play important roles in feedback regulation of GPCRs, such as of β-adrenergic receptors in the heart, where GRK2 and GRK5 are the major isoforms expressed. Membrane targeting is essential for GRK function in cells. Whereas GRK2 is recruited to the membrane by heterotrimeric Gβγ subunits, the mechanism of membrane binding by GRK5 is not fully understood. It has been proposed that GRK5 is constitutively associated with membranes through elements located at its N-terminus, its C-terminus, or both. The membrane orientation of GRK5 is also a matter of speculation. In this work, we combined sum frequency generation (SFG) vibrational spectroscopy and attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR) to help determine the membrane orientation of GRK5 and a C-terminally truncated mutant (GRK51-531) on membrane lipid bilayers. It was found that GRK5 and GRK51-531 adopt a similar orientation on model cell membranes in the presence of PIP2 that is similar to that predicted for GRK2 in prior studies. Mutation of the N-terminal membrane binding site of GRK5 did not eliminate membrane binding, but prevented observation of this discrete orientation. The C-terminus of GRK5 does not have substantial impact on either membrane binding or orientation in this model system. Thus, the C-terminus of GRK5 may drive membrane binding in cells via interactions with other proteins at the plasma membrane or bind in an unstructured manner to negatively charged membranes.